ศาสนาพุทธกับรัฐศาสตร์ - นีละโยธิน, อัครเดช (วารสารมหาวิทยาลัยมหามกุฏราชวิทยาลัย วิทยาเขตอีสาน; Vol 1 No 2 (2020): พฤษภาคม - สิงหาคม 2563, 2020)
บทคัดย่อ บทความวิชาการฉบับนี้มุ่งศึกษาความสัมพันธ์ระหว่างศาสนาพุทธกับรัฐศาสตร์ โดยศาสนาพุทธเป็นรากฐานของสังคมไทยหรือวัฒนธรรมไทย และความเป็นชาติไทย ตลอดจนเอกลักษณ์ของชาติ ทั้งทางด้านสังคม และการเมือง เริ่มจากการดำเนินชีวิตของคนไทยมีความผูกพันกับพระพุทธศาสนา ตลอดจนแนวความคิด จิตใจ และกิจกรรมแทบทุกอย่างในชีวิต ตั้งแต่เกิดจนตาย อีกทั้งพระมหากษัตริย์ของไทยยังคงใช้หลักธรรมของศาสนาพุทธในการปกครองแผ่นดินให้มีความผาสุกเป็นต้นมา และประชาชนในสังคมไทยก็ได้นำหลักธรรมมายึดเป็นแนวในประพฤติปฏิบัติทำความดี มีศีลธรรมอันดีในการทำมาหากินเลี้ยงชีพ การร่วมอยู่กับสังคม และการช่วยเหลือซึ่งกันและกัน เป็นหลักในการปกครองบ้านเมือง กษัตรีย์ทุกพระองค์นำเอาหลักธรรมพระพุทธศาสนามาใช้ในการปกครองบ้านเมือง เป็นศูนย์รวมจิตใจของประชาชนคนไทย เพราะศาสนาพุทธสอนให้รักสามัคคี มีเมตากรุณาต่อกัน เป็นที่รากฐานทางวัฒนธรรมไทย ดังนั้นในการปกครองบ้านเมืองจะสงบสุขและเจริญรุ่งเรือง ผู้นำ ผู้ปกครอง ประชาชน จะต้องมีคุณธรรม จริยธรรม ควบคู่กันไปด้วย นั้นคือการนำศาสตร์ทางศาสนาพุทธและศาสตร์ทางรัฐศาสตร์ผสมผสานในเรียนรู้ การนำไปบริหารบ้านเมือง ในการปกครองบ้านเมือง หรือที่เรียกว่า รัฐศาสตร์ตามแนวพระพุทธศาสนา และเดินตามรอยพระยุคลบาทที่ท่านทรงใช้หลักทศพิธราชธรรม หรือ ราชธรรม ๑๐ คือจริยวัตร ๑๐ ประการที่พระเจ้าแผ่นดินทรงประพฤติเป็นหลักธรรม ประจำพระองค์ หรือเป็นคุณธรรมประจำตนของผู้ปกครองบ้านเมือง ให้มีความเป็นไปโดยธรรมและยังประโยชน์สุขให้เกิดแก่ประชาชนจนเกิดความชื่นชมยินดี ซึ่งความจริงแล้วไม่ได้จำเพาะเจาะจงสำหรับพระเจ้าแผ่นดินหรือผู้ปกครองแผ่นดินเท่านั้น บุคคลธรรมดาที่เป็นผู้บริหารระดับสูงในทุกองค์กรก็พึงใช้หลักธรรมเหล่านี้   Abstract This academic journal studies about the relation between Buddhist and political science that Buddhist, Thai culture, being Thai or identity of Thai nation in the part of society and politics which one is the foundation of Thai society. The lifestyle of Thai people, their concept, their mind and their activities since they were born until died, has had relationship with Buddhist. Also, the kings of Thailand have been bringing the dharma principle of Buddhist to administrate the reign to be the honest reign. Thai citizens also bring this principle in ways of the practice of their life, the moral in their occupations, living with one another and helping each other, so this is the principle of administration of our nation. Every king of Thailand has been bringing this principle to administrate the country and gather the Thais moral because Buddhist educates Thai people to love, to harmonize and to have mercy with each other, this is the foundation of Thai society. Therefore, the administration of country to be peacefully and civilized, the chief, the leaders and the citizens must have virtues and morality. This is the science of Buddhist and political science that bring them together for learning how to manage and administrate the country, we know as political science in the way of Buddhist from tenfold virtues of the ruler (Dasavidha - rajadhamma) or ten virtues of practice that the kings have been bringing to be the principle or the virtue of administer to administrate the country to be honest, to make the good things happen to all citizens and to make them have the happiness. In actually, it is not only the kings or the administer , but also the people who are the chiefs in organizations should learn to use these virtues.